Current Trends and Future Directions in Prosthetic and Implant Dentistry in the Digital Era - Di Fiore, Adolfo; Brunello, Giulia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Advancements in digital technologies are reshaping the world of dentistry, from prosthodontics to implant dentistry. Intraoral scanners, facial scanners, 3D printers, and milling machines have revolutionized the clinical approach and operative workflow in daily practice. However, digital dentistry brings several challenges to clinicians due to the rapid evolution of new technologies and the lack of evidence-based guidelines for their correct use. The aim of this Special Issue is to cover the latest advances in the development and application of digital technologies in prosthetic and implant dentistry. We wish to provide both clinicians and researchers with a comprehensive and up-to-date source of information on current trends, limitations, and potential future applications of digital technologies in daily clinical practice.